iFPH: WIRELESS CONTROL OF SOUND - Adrian BORZA (Studia Universitatis Babeş-Bolyai. Musica, 2012)
A wireless interactive music system is a powerful tool for creating and performing music on stage. It combines different pieces of hardware and software, and the computer is controlled through a nano control surface or even a smartphone mediated by a nano wireless router. This study focuses on the Max patch for connecting a Wi-Fi device to the iFPH music software.